Research on cooling-temperature control strategy of fuel-cell engine test bench. Issue 1 (24th February 2023) - Du, Chang; Ma, Tiancai; Lin, Weikang; Song, Kaihang; Liang, Yonghao
Abstract: As one of the important ways to utilize hydrogen energy, fuel cells are receiving more and more attention and research from countries and institutions. To meet the practical needs of testing the performance of high-power fuel-cell systems and simulate the actual application environment as much as possible, a fuel-cell system test bench is usually used to test the system performance, in which the cooling-temperature control of the test bench has a great impact on the results of the performance of the fuel-cell system. This paper studies the cooling-temperature control strategy of a 150-kW-class fuel-cell engine test platform, proposes a new test-bench cooling-system structure with a thermostat and heat exchanger as the main heat-dissipation components, and compares and analyzes the impact of coordinated thermostat and heat-exchanger control on the fuel-cell system test performance. The test results show that the control strategy of the coordinated operation of a thermostat and heat exchanger can maintain the steady-state error to within ±0.3℃ and maintain the temperature variation to within ±1.5℃ during the loading-condition test, so as to avoid the limitation of system output performance due to excessive cooling-temperature fluctuation and ensure that the fuel-cell engine performance-test process is carried out smoothly and efficiently. Graphical Abstract: Abstract : This paper proposes a new bench-scale cooling system for a fuel-cell engine test platform, which comprises a thermostat and heat exchanger as the main heat-dissipation component. The coordinated control strategy maintains the steady-state error to within ±0.3℃ and the temperature variation to within ±1.5℃ at load.